Types Of Interactive Methods And Their Implementation To Improve The Quality Of Education (Journal of Pedagogical Inventions and Practices, 2024)
The article deals with the importance of teaching the student with the help of interactive methods, feeling successful, feeling his intellectual ability, effectively organizing the learning process, and improving knowledge and skills. The author notes that when employing interactive methods, the teacher's role is to organize the process by preparing tasks in advance, formulating questions or discussion topics for groups, offering advice, and managing the time and order of executing the planned activities.